The Types of Anxiety in Argumentative Writing of English Class - Rizki Chamilia Santi; Tatik Irawati (ELITE JOURNAL, 2023)
This study aims to identify the types of anxiety that occur in argumentative writing. The phenomenon of qualitative descriptive data aims to identify writing anxiety faced by the fourth semester students of English education and the level of student's writing skills. Data were collected from Second Language Writing Anxiety Inventory (SLWAI) questionnaire from Cheng with 20 students' assignments, interviews with five students, and observations. The most common types of anxiety levels can be seen in questionnaires, assignments, and student assignments interviews. That type of anxiety avoidance behavior is supreme. In this case, the highest students' writing anxiety is cognitive, which affects writing or actions taken in class. Keywords: Anxiety, Argumentative Writing, Writing Ability.